Cental Macular Thickness in Patients with Type 2 Diabetes Mellitus without Clinical Retinopathy. (3rd April 2013) - Demir, Mehmet; Dirim, Burcu; Acar, Zeynep; Yılmaz, Murat; Sendul, Yekta
Abstract : Objective . To compare central macular thickness (CMT) of diabetic patients with type 2 diabetes without clinical retinopathy and healthy subjects. Materials and Methods . Optical coherence tomography (OCT) measurements were performed in 124 eyes of 62 subjects with diabetes mellitus without clinical retinopathy (study group: 39 females, 23 males; mean age: 55.06 ± 9.77 years) and in 120 eyes of 60 healthy subjects (control group: 35 females, 25 males; mean age: 55.78 ± 10.34 years). Blood biochemistry parameters were analyzed in all cases. The data for central macular thickness (at 1 mm), the levels of fasting plasma glucose, and glycosylated hemoglobin (HbA1c) were compared in both groups. Results . The mean central macular thickness was 232.12 ± 24.41 µm in the study group and 227.19 ± 29.94 µm in the control group. The mean HbA1c level was 8.92 ± 2.58% in the study group and 5.07 ± 0.70% in the control group (P = 0.001 ). No statistically significant relationship was found between CMT, HbA1c, and fasting plasma glucose level in either group (P > 0.05 ). Conclusions . Central macular thickness was not significantly thicker in patients with type 2 diabetes without clinical retinopathy than in healthy subjects.